Segmentasi Citra Ct Scan Paru-Paru Dengan Menggunakan Metode Active Contour - Nurul Fadillah; Chicha Rizka Gunawan (JURIKOM (Jurnal Riset Komputer), 2019)
The lungs are one of the important organs in the human body. Because the lungs are one of the holders of control in the circulatory system in the human body. According to some internal medicine specialists, the lungs are the most vulnerable internal organs to damage, this is due to lung function that comes in direct contact with the outside environment such as inhaled cigarette smoke, vehicle fumes, or is allergic to something. So that the lungs are hollow and eroded. Therefore detection of human lungs is needed. To find out damage to the lungs, a CT scan image process is needed. In CT-Scan images there is information that is used to analyze and know the shape of an object from the lung itself. To obtain this information, it is necessary to do a segmentation process. In this study using the Active Contour method. Active Contour is a segmentation method that is often used because this method uses a closed curve model that can move wide or narrow. The purpose of this study was to segment the lungs on CT-Scan images by using the active contour method to determine the value of the area and perimeter of the lung section that was good and to find the accuracy value of the method used for a CT-Scan image. The results of lung segmentation were carried out a system trial carried out on 15 CT-Scan image data obtained an average accuracy of 80%